The Instructional Role of Elementary School Principals - Mitchell, Coral; Castle, Joyce (Canadian Journal of Education/Revue canadienne de l’éducation, 2005)
To study elementary school principalsʹ understandings and enactments of instructional leadership, we collected data through individual interviews, focus‐ group discussions, and in‐school observations. Three categories captured principalsʹ conceptualizations of instructional leadership: curriculum expertise, formal delivery of professional development, and informal culture building. Their enactment of instructional leadership was influenced by three dimensions: their personal style, degree of coherence in agendas and initiatives, and availability of enabling structures. We anticipated the influence of personal style, but not the impact of coherence and structure, which introduces a new dimension to the literature on contextual influences impinging on individual practice Keywords: school improvement, educational leadership, professional development, school culture Pour étudier la conception et la mise en œuvre du leadership pédagogique chez des directeurs et directrices d’école, les auteures ont colligé des données au moyen d’entrevues individuelles, de discussions en groupe et d’observations sur place. La conception du leadership pédagogique des directeurs et directrices d’école a été analysée à l’aide de trois catégories : expertise en matière de programmes scolaires, prestation de services de perfectionnement professionnel et édification d’une culture informelle. La mise en œuvre du leadership pédagogique a été étudiée pour sa part à l’aide de trois volets : style personnel, degré de cohérence dans les calendriers et les initiatives et mise en place de structures d’incitation. Les auteures avaient prévu l’influence du style personnel, mais non l’impact de la cohérence et des structures, ce qui introduit une nouvelle dimension dans la littérature au sujet des influences contextuelles sur la pratique de chacun. Mots clés : amélioration scolaire, leadership en éducation, perfectionnement professionnel, culture de l’école.